Implementation of Solar Heat Energy and Adsorption Cooling Mechanism for Milk Pasteurization Application - G. Ramkumar; B. Arthi; S. D. Sundarsingh Jebaseelan; M. Gopila; P. Bhuvaneswari; R. Radhika; Geremew Geidare Kailo (Adsorption Science & Technology)
The use of renewable energy is crucial to the global growth of sustainability. Milk business amongst many other food industry divisions requires a significant amount of energy, making the meal processing business one of the most energy-intensive industries. As of right now, more than 30 percent of the dairy produced in India is processed. In distant parts of India, milk spoiling is more common due to the delay among milking and storing; as a result, facilities for quick pasteurization and storage are needed. Heated is necessary for pasteurization. Since for a long time, the Indian milk industry has relied on nonrenewable energy sources, that are not only becoming much more costly but are also to blame for significant environmental issues including greenhouse gases and health issues. Consequently, scientific communities, environmental and social organizations, and the governments have all pushed the use of green energy. Solar energy has been shown to be the most viable among various sustainable and renewable energies given the geographical position of India. Solar energy can be used to pasteurize milk because of the energy intensity and range of temperature requirements. Adsorbent refrigerator is recommended here since it is powered by waste/solar heat and can store (200 liters of milk) at low temperatures until it is distributed after the pasteurization process (easily available from farm waste). The solar collector of evacuated tube is used for minimizing heat loss and pasteurizing milk. The outcome demonstrates that milk can be simply pasteurized at 73°C for 25minutes at a flow rate of 5 liter per minutes. A solar energy adsorbent refrigeration system has been constructed and described for keeping 200 liters of milk at 10-15°C for 9–11 hours. Investigation findings indicate that the specific cooling power of the system is sufficient to store 200 liters of milk at 5.8 kW/kg and 5.5 kW/kg for 500 liter per hours hot water supplied at 92°C, 32°C condenser temperatures, and 5°C evaporator temperatures. The heat loss of evacuated tube collector is compared to solar concentrator. The study results provide evacuated tube collector is better for pasteurizing milk since to its highly efficient, longevity, and compactness.